Long-term results of the DelIVery for Pulmonary Arterial Hypertension trial. (November 2019) - Gomberg-Maitland, Mardi; Bourge, Robert C.; Shapiro, Shelley M.; Tarver, James H.; Zwicke, Dianne L.; Feldman, Jeremy P.; Chakinala, Murali M.; Frantz, Robert P.; Torres, Fernando; Bag, Remzi; Murphy, Jeffrey A.; Lautenbach, Amy A.; et al.
Background: The DelIVery for Pulmonary Arterial Hypertension clinical trial was a multi-center, prospective, single arm, Investigational Device Exemption study utilizing a fully implantable, programmable intravascular delivery system consisting of a pump and a catheter for intravenous treprostinil. The study met its primary endpoint and demonstrated that the intravascular delivery system significantly reduced catheter related complications at 22, 000 subject-days of follow-up compared with a predefined objective performance criterion. Here we summarize the results obtained during a 6.4-year follow-up period. Methods: Throughout study follow-up, participants had clinic visits and medication refills at least every 12 weeks (dependent on the subjects' dose). All adverse events and intravascular delivery system complications were evaluated and recorded. Results: Sixty pulmonary arterial hypertension subjects were followed post device implantation for approximately 282 patient-years (range 87 days to 6.4 years). Of the 60 subjects, 14 died (1 related to intravascular delivery system pump failure), 2 withdrew after lung transplants, and 2 withdrew due to pump pocket infection. No catheter-related bloodstream infections, catheter thrombosis or occlusions, or catheter kinks occurred through 282 patient-years. Two participants had adverse events of abdominal pain, rash, due to subcutaneous treprostinil "leaks" after one catheter puncture and one catheter laceration during pump refill and replacement, respectively. Eight pump failure events occurred: seven pump motor stalls and one early replacement (faulty battery). Conclusion: Delivery of treprostinil with an intravascular delivery system is a safe alternative to an external delivery system, while providing enhanced life experiences. To preserve the risk–benefit ratio, treatment at specialized pulmonary arterial hypertension centers is recommended until training is disseminated at other sites.